A comprehensive usability study of 3D printing slicer software: Integrating SUS, USE questionnaire, and key UX dimensions - Wibowo, Astrid Wahyu Adventri; Ismianti, Ismianti; Husaini , Rochmat; Mastrisiswadi , Hasan; Kasih, Puji Handayani; Rahmawati, Keny; Atsani , Sarah Iftin (OPSI, 2025)
This study evaluates the usability of three widely used 3D printing slicer software, Ultimaker Cura, IdeaMaker, and PrusaSlicer, at the Engineering Drawing Laboratory of UPN “Veteran” Yogyakarta. A mixed-methods approach was applied, combining the System Usability Scale (SUS) and the USE Questionnaire (Which Assesses Usefulness, Ease of Use, Ease of Learning, and Satisfaction), as well as direct observation of three UX dimensions: learnability, effectiveness, and efficiency. Nine respondents completed seven task scenarios, each with six repetitions. To compare the three software, statistical analysis was conducted using the Friedman test and Wilcoxon post-hoc comparisons. The results showed that Ultimaker Cura consistently achieved the highest SUS and USE scores and demonstrated significantly faster task completion times. The strong alignment between observed performance and user perception supports the validity of the blended evaluation method. This study concludes that Ultimaker Cura is the most user-friendly option for beginners and is well-suited for educational environments. This finding contributes to provide guidance in selecting software and teaching practices in educational laboratories, while also contributing to usability research.